2022
DOI: 10.1186/s13045-022-01272-w
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-PACERR induces pro-tumour macrophages via interacting with miR-671-3p and m6A-reader IGF2BP2 in pancreatic ductal adenocarcinoma

Abstract: Background LncRNA-PACERR plays critical role in the polarization of tissue-associated macrophages (TAMs). In this study, we found the function and molecular mechanism of PACERR in TAMs to regulate pancreatic ductal adenocarcinoma (PDAC) progression. Methods We used qPCR to analyse the expression of PACERR in TAMs and M1-tissue-resident macrophages (M1-NTRMs) which were isolated from 46 PDAC tissues. The function of PACERR on macrophages polarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 53 publications
(45 reference statements)
2
49
0
Order By: Relevance
“…The accuracy of these 10 miRNAs to predict tumor recurrence after surgery or liver transplantation in patients with HCC was verified using an external validation dataset (GSE30297) and an internal validation dataset (TCGA). Multiple previous studies have shown that these 10 miRNAs are associated with multiple malignancies, including hepatocellular carcinoma, gastric cancer, and pancreatic ductal adenocarcinoma [ 12 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of these 10 miRNAs to predict tumor recurrence after surgery or liver transplantation in patients with HCC was verified using an external validation dataset (GSE30297) and an internal validation dataset (TCGA). Multiple previous studies have shown that these 10 miRNAs are associated with multiple malignancies, including hepatocellular carcinoma, gastric cancer, and pancreatic ductal adenocarcinoma [ 12 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent accumulating researches reported that ncRNAs can regulate downstream target genes through interacting with m6A modulators (writers, erasers, readers). For example, PACERR, an upregulated lncRNA in pancreatic ductal adenocarcinoma (PDAC), contributes to increasing the number of M2-polarized cells and facilizing the malignant phenotype in PDAC by binding to m6A reader IGF2BP2 to increase the stability of downstream target genes KLF12 and c-myc [ 82 ].…”
Section: The Biological Role Of M6a-modified Ncrnasmentioning
confidence: 99%
“…PACERR acts as amiR-671-3p sponge to activate the KLF12/AKT/c-myc pathway and it also enhances the stability of KLF12 and c-myc by interacting with insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2). KLF12 can directly bind to the promoter of PACERR, and KLF12-transcribed PACERR recruits histone acetyltransferase E1A binding protein p300 (EP300) to increase the acetylation of histone (H3K27) in the PACERR promoter region and enhance the transcription of PACERR in TAM ( 48 ). Notably, PTGS2 and PACERR have overlapping promoter regions, and PACERR is transcribed in the opposite direction of PTGS2; thus, PACERR functions as a cis -acting lncRNA in TAM.…”
Section: Lncrnas Regulate Tams and Influence Tumorigenesis And Progre...mentioning
confidence: 99%